Kawasaki disease presenting as acute intestinal obstruction - Yasir Ahmad Lone; Jagadeesh Menon; Prema Menon; Kim Vaiphei; Katragadda Lakshmi Narasimha Rao; Baburam Thapa; Kirti Gupta (Wolters Kluwer Medknow Publications, 2017)
Kawasaki disease (KD) is an acute febrile illness of childhood associated with vasculitis of medium-sized arteries especially the coronary arteries. Typical clinical features involving the skin, mucous surfaces, etc., occur sequentially over a few days. We report a rare presentation of KD as a surgical abdomen in a 2-year-old boy. Awareness of this presentation is important as it can otherwise lead to a delay in starting potentially life-saving intervention like intravenous immunoglobulins for cardiac complications kept cryptic by the manifest acute abdomen.